Synthesis of constraints to livestock research and development and recommendations - Mgheni, M.; Mukhebi, A.W.; Setshwaelo, L.L.; Tsiresy, P.; Nyathi, P.; Osuji, P.O.; Kategile, J.A. (International Livestock Centre for Africa, 1993)
This report is a synthesis of the workshop and covers the major constraints to improving livestock production ystems in the subregion (East and Southern Africa) and includes a set of recommendations for follow-up action. Discusses the changing agricultural systems in the region, livestock production systems, major constraints, long-term nature of livestock programmes, monitoring, programme development, implementation strategy and follow-up action.